2019
DOI: 10.3389/fmicb.2019.00599
|View full text |Cite|
|
Sign up to set email alerts
|

Microbiota of the Gut-Lymph Node Axis: Depletion of Mucosa-Associated Segmented Filamentous Bacteria and Enrichment of Methanobrevibacter by Colistin Sulfate and Linco-Spectin in Pigs

Abstract: Microorganisms are translocated from the gut to lymphatic tissues via immune cells, thereby challenging and training the mammalian immune system. Antibiotics alter the gut microbiome and consecutively might also affect the corresponding translocation processes, resulting in an imbalanced state between the intestinal microbiota and the host. Hence, understanding the variant effects of antibiotics on the microbiome of gut-associated tissues is of vital importance for maintaining metabolic homeostasis and animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 126 publications
1
9
1
Order By: Relevance
“…In taking into account that mucosaassociated bacteria utilize host mucin as the substrate (24), greater luminal substrate availability may explain the higher bacterial richness and total bacterial gene copy number in ileal digesta than in the mucosa. In contrasting previous studies (25)(26)(27), Clostridiaceae and Lactobacillaceae were the predominant taxa at all three ileal sites, implying the importance of the luminal bacteria for colonization of the mucosa and translocation into ICLNs in the present pigs. Previously, Kelly et al (25) reported a predominance of Helicobacteraceae and Campylobacteraceae at the ileal mucosa, which were less abundant in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In taking into account that mucosaassociated bacteria utilize host mucin as the substrate (24), greater luminal substrate availability may explain the higher bacterial richness and total bacterial gene copy number in ileal digesta than in the mucosa. In contrasting previous studies (25)(26)(27), Clostridiaceae and Lactobacillaceae were the predominant taxa at all three ileal sites, implying the importance of the luminal bacteria for colonization of the mucosa and translocation into ICLNs in the present pigs. Previously, Kelly et al (25) reported a predominance of Helicobacteraceae and Campylobacteraceae at the ileal mucosa, which were less abundant in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Specific bacterial subsampling or translocation was also obvious for Methanobacteriaceae, whose abundance largely increased from digesta to the mucosa and into the ICLNs. Although this is in line with our recent findings (27), like for many other bacteria found in ICLNs, little is known about their metabolic role and impact on the host. Theoretically, Methanobacteriaceae may have benefited from cross-feeding relationships with eubacteria, as they obtain their energy for growth mostly from the reduction of CO 2 and formate with H 2 , or, in the case of Methanosphaera, from the reduction of methanol with H 2 (32).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…At present, molecular methods, e.g., PCR, genome sequencing, and MALDI-TOF MS enable definitive diagnosis, along with geographical distribution studies, virulence profile, and genetic diversity investigation of Corynebacterium species from domestic animals worldwide, including C. pseudotuberculosis strains [2,7,8,[31][32][33][34]. In the coming years, large-scale sequencing has seen used to investigate the microbiota of lymph nodes from humans [35] and animals (pigs) [36], with the aim to diagnose and differentiate agents/diseases; however, this next generation sequencing method has not yet been applied in the investigation of lymph nodes from sheep with and without lesions compatible with CL.…”
Section: Discussionmentioning
confidence: 99%